Efficacy of intralesional bleomycin in treatment of lymphangiomas in children: an observational study - Ainippully, Arun M.; P., Ranjit; V., Arun Preeth; S., Prathap (International Surgery Journal, 2017)
Background: Lymphangioma, a benign slow growing tumor of lymphatic vessels, common to the pediatric age group usually presents as swelling with cosmetic deformity. Commonly affecting the head and neck region it may present with compressive symptoms like airway obstruction or dysphagia. Previously surgical excision was the treatment of choice but it involves significant risks and so sclerotherapy has gained popularity. We conducted this prospective observational study to hava a quantitative analysis of the effect of intralesional bleomycin in reducing the size of lymphangiomas in children in our setup. Methods: This observational study was conducted in the paediatric surgery department between 2014 and 2016. A total of 34 children who presented with swellings which were diagnosed to be lymphangiomas based on clinical and sonological basis were included in the study and underwent intralesional bleomycin sclerotherapy. Details like dimensions of the lesion before and after the treatment, ultrasound measurement, residual size, characteristic of the cyst like presence or absence of septation, micro or macrocytic were recorded along with demographic details like age and sex. Outcome after 4 weeks was evaluated and classified into 3 groups as in excellent response, good response or poor response. Statistical analysis was done using R statistical software. Results: Of the 34 patients 59% were males. The median age was 18 months with inter-quartile range 4-36 months. 88% of patients had macrocystic lesions. 4 weeks after bleomycin sclerotherapy excellent response was seen in 23 (68%) of the patients, good in 8 (26%) and poor in 3 (9%) of the patients. There was statistically significant association between post procedure swelling, type of cysts and presence of septations and the number of sittings required to the outcome (p value <0.05). Conclusions: Present study shows that intralesional bleomycin sclerotherapy is very effective in the treatment of lymphangiomas in children, with macrocystic lesions showing a significantly better response.